Validity and Practicality of Ongoing Assessment using STEM Approach Based Multiple Representation and Integrated with 21st Learning - Indah Permatasari; I Wayan Distrik; Undang Rosidin (Jurnal Pembelajaran Fisika, 2021)
The purpose of this research is to use science, technology, engineering and mathematics (STEM) methods for effective and practical ongoing assessment, which is based on multiple representations and combined with the 21st learning magnetic field ability of Indonesian Lampung Bandar Lampung High School students. This ongoing assessment development adapted the Borg and Gall development model, which was grouped into four stages, such us: preliminary research stage, planning and development stage, the field test stage, and the dissemination stage. The research sample was 30 grade XI high school students who were taken randomly. Data collection techniques can use questionnaires, observation sheets, and tests. The data analysis technique used a qualitative approach with descriptive analysis techniques. The results showed that the ongoing assessment with stem approach multiple representations based integrated to 21st-century learning was stated: (1) valid, covering an average valid content of 83.38% and average construct validity of 78.33% (2) practical, including readability, easy to apply in learning and got positive responses from the student, stated practical with an average percentage of 83.40%.Keywords: Multiple Representations, on-Going Assessment, and STEM ApproachDOI: http://dx.doi.org/10.23960/jpf.v9.n2.202102